Extracorporeal life support is safe in trauma patients. Issue 1 (January 2017) - Burke, Christopher R.; Crown, Angelena; Chan, Titus; McMullan, D. Michael
Abstract: Introduction: The role of extracorporeal life support (ECLS) in the critically ill trauma patient is poorly defined, possibly leading to the underutilization of this lifesaving therapy in this population. This study examined survival rates and risk factors for death in trauma patients who received ECLS. Methods: Data from the National Trauma Data Bank was retrospectively reviewed to identify trauma patients who received ECLS from January 2012 to December 2014. Clinical outcomes and risk factors for death were examined in these patients. Results: Eighty patients were identified and included in the final analysis. Overall survival to hospital discharge was 64%. Survivors and non-survivors were similar in regard to age, gender, weight, and injury mechanism. Non-survivors had greater median injury severity scores (ISS) (29 non-survivors vs. 24 survivors, p = 0.018) and had a shorter median total hospital length of stay (8 days non-survivors vs. 32 days survivors, p < 0.001). Analysis of specific anatomic locations of traumatic injury, including serious head/neck, thoracic, and abdominal injuries, revealed no impact on patient survival. Multivariable logistic regression analysis identified increasing age and ISS as significant risk factors for mortality; whereas treatment at facilities that performed multiple ECLS runs over the study period was associated with improved survival. Conclusions: Extracorporeal life support appears to be an effective treatment option in trauma patients with severe cardiopulmonary failure. Survival in trauma patients receiving ECLS is similar to that observed in the general ECLS population and this may represent an underutilized therapy in this population.